Pengaruh Kombinasi Counter Pressure dan Terapi Musik Terhadap Penurunan Nyeri Punggung Pada Ibu Bersalin Kala 1 di Klinik Siti Nugraha Medika Tahun 2024 - Amalia Indah Puspitasari; Arti Wulansari (Jurnal Ners, 2025)
Back pain is one of the main complaints experienced by mothers in the first stage of labor, caused by uterine contractions, opening of the cervix, and changes in the position of the fetus in the birth canal. This study aims to analyze the effect of a combination of counter pressure and music therapy on reducing back pain in mothers in the first stage of labor. Analyzing the effect of a combination of counter pressure techniques and music therapy on reducing the intensity of back pain in mothers in the first stage of labor at the Siti Nugraha Medika Clinic. This research uses quantitative methods with a quasi-experimental pretest-posttest design. The research sample consisted of 30 mothers who met the inclusion criteria. Pain level measurement was carried out using the Numeric Rating Scale (NRS). The data were analyzed using the Paired Sample T-Test. There was a significant influence between the pre-test and post-test pain levels and values ​​(p = 0.000). Before the intervention, the majority of respondents experienced severe pain (52.8%), while after the intervention, the majority experienced moderate pain (56.1%). The combination of counter pressure and music therapy has proven to be effective in reducing the intensity of back pain, with an average reduction of 1.93 points. The combination of counter pressure and music therapy can be a safe, simple and effective non-pharmacological method for reducing back pain in mothers in the first stage of labor, as well as increasing comfort during the labor process.